The role of global production networks (GPN) in understanding the impacts of the United States' and China's macroeconomic stimulus on the ASEAN economies - Conchada, Mitzie Irene P. (Animo Repository, 2012)
The economic performance of the Association of Southeast Asian Nations (ASEAN) has been growing fast due to the utilization of Global Production Networks (GPNs) facilitated by liberalization, deregulation, and impact of information and communication technology (ICT). In the midst of the global financial crisis, ASEAN is affected by the downturns in the global economy especially with the United States (US). As shocks are introduced to global trade, ASEAN will be influenced significantly especially the region's most open economies, whose exports represent a substantial percentage of its Gross Domestic Product (GDP). China, where ASEAN has a trade surplus due to exports of raw materials and component electronics and computer parts for re-export is deemed to be the key in sustaining the region's economies. This suggests that nations are really interdependent with each other and that no single economy can decouple from the rest of the world in terms of economic performance. For instance, a drop in China's exports to the rest of the world will have negative consequences on the ASEAN economies that supply the necessary raw materials that China will require for exports to the rest of the world specifically in US. Vector Autoregression (VAR) was implemented to investigate the vulnerability of trade between US, China, and ASEAN. It generally revealed that these economies are indeed interdependent of each other especially in trade, responsible for their economic growth. Results also show that the economic growth experienced by ASEAN brings about positive effects to China's exports sector since ASEAN is the major supplier of raw materials and one of the major importers of China's exports. Therefore, ASEAN needs to open up further for trade and ensure that the strong linkages within the region are not weakened by trade barriers. There is also a need to deepen the regional cooperation efforts in macroeconomic coordination, deepening of development cooperation initiatives in capacity building, human resource development, research and development, and trade and investment facilitation. Copyright © 2012 De La Salle University, Philippines.